The Complex Relationship between Violence and Religion: A Response to William T. Cavanaugh’s “Girard and the Myth of Religious Violence” - Steinmair-Pösel, Petra (Does religion cause violence?, 2018)
As the title of William T. Cavanaugh’s book, The Myth of Religious Violence, indicates, the political theologian advances the hypothesis that the notion of specifically and substantially “religious” violence—especially if seen in contrast to allegedly secular nonviolence—is a myth. He does so by resorting to a mostly historical argument, keeping theology in the background in order to address an audience as wide as possible. On the other hand, one of the cultural anthropologist René Girard’s main works bears the title Violence and the Sacred and has inspired the foundation of an international academic society calling itself the “Colloquium on Violence and Religion” (COVR), thus implying a substantial relationship between religious phenomena and violence....